Development of Apparel Products from Eri and Ramie Blended and Union Fabrics - Tamta, Meenakshi; Mahajan, Surabhi (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted in the Department of Apparel and Textile Science, College of Community Science, Punjab Agricultural University during 2019–2022. The objective of the investigation was to develop apparel products viz. men’s waist coat, ladies top and men’s jacket from eri and ramie blended and union fabrics according to the end use specifications opined by a panel of judges. The commercial viability of the developed end products was also analyzed through a survey based on consumer’s outlook. The consumers were highly appreciative of the developed products and in terms of aesthetic properties, men’s waist coat was found to be excellent whereas ladies top and men’s jacket were found to be very good. As far as overall ranking of the products was concerned, waist coat was considered as the best as compare to men’s jacket and ladies’ top. The price suitability of all the developed products was also found to be appropriate among the consumers. So, the study recommends that proper utilization of eri and ramie fibres in the form of attractive handloom apparel products that will add to its commercial value and also lead to diversification in the market. This study will also inspire fashion designers and manufacturers for the development of unique eco-friendly range of products from natural fibers as the developed products were found to have very good consumer response.